Madagascar - Building Leadership and Management Capacity through the Rapid Results Approach - Mastri, Lawrence (2012)
In 2002 Madagascar's new government under President Mark Ravolamana recognized the urgency of addressing the peoples' high expectations for concrete economic and social improvements. While it rushed to put the economy back on track and improve the quality of life, its vision and strategy for reform was no match for the realities on the ground. By the time the Ravolamanana government assumed power in 2002, GDP had declined by 13 percent, key public services were discontinued, and the poverty rate soared from 69 percent in 2001 to 80 percent. There was widespread joblessness and high inflation. Within the government, there was little capacity for policy planning or monitoring and evaluation in most sectors. Collaboration was weak, with no existing mechanism to allow for a joint ministerial response to problems that cut across sectors. In February 2005, when the government launched its first rapid results pilot, the goal was to mitigate the effects of a significant shortfall in rice production, importation, and distribution. The crisis was solved by a combination of policy-based and technical interventions. Rice production increased significantly in two of the four targeted regions when the rapid results approach (RRA) was applied. In the region of Boeny, production went from 2.5 tons per hectare in 2004 to 4 tons per hectare in 2005, and in the region of Menabe, it increased from 22,000 tons to 37,000 tons.